2018
DOI: 10.1111/dom.13587
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic efficacy and safety of linagliptin compared to a basal‐bolus insulin regimen in patients with type 2 diabetes undergoing non‐cardiac surgery: A multicentre randomized clinical trial

Abstract: Aims: The use of incretin-based therapy, rather than or complementary to, insulin therapy is an active area of research in hospitalized patients with type 2 diabetes (T2D). We determined the glycaemic efficacy and safety of linagliptin compared to a basal-bolus insulin regimen in hospitalized surgical patients with T2D. Materials and Methods:This prospective open-label multicentre study randomized T2D patients undergoing non-cardiac surgery with admission blood glucose (BG) of 7.8 to 22.2 mmol/L who were under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 31 publications
2
52
0
6
Order By: Relevance
“…In addition to iatrogenic hypoglycaemia, the significant workload associated with continuous insulin infusion and multiple daily insulin injections has led to an increased use of non‐insulin agents to manage patients with diabetes in hospital 27 . As an alternative to intensified insulin regimens, our group and others have reported on the use of DPP‐4 inhibitors for the management of inpatients with diabetes 15,16,27,28 . Recent RCTs have reported that treatment with DPP‐4 inhibitors alone or in combination with basal insulin in general surgery patients results in improved glycaemic control with a lower risk of hypoglycaemia compared with a basal bolus insulin regimen 15,16,28 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to iatrogenic hypoglycaemia, the significant workload associated with continuous insulin infusion and multiple daily insulin injections has led to an increased use of non‐insulin agents to manage patients with diabetes in hospital 27 . As an alternative to intensified insulin regimens, our group and others have reported on the use of DPP‐4 inhibitors for the management of inpatients with diabetes 15,16,27,28 . Recent RCTs have reported that treatment with DPP‐4 inhibitors alone or in combination with basal insulin in general surgery patients results in improved glycaemic control with a lower risk of hypoglycaemia compared with a basal bolus insulin regimen 15,16,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of noninsulin glucose-lowering therapies in the hospital setting is an area of active research (57,58). Several recent randomized trials have demonstrated the potential effectiveness of glucagon-like peptide 1 receptor agonists and dipeptidyl peptidase 4 inhibitors in specific groups of hospitalized patients (59)(60)(61)(62). However, an FDA bulletin states that providers should consider discontinuing saxagliptin and alogliptin in people who develop heart failure (63).…”
Section: Noninsulin Therapiesmentioning
confidence: 99%
“…There are limited data available about the efficacy and safety of non-insulin agents in hospitalized patients, almost restricted to dipeptidyl peptidase 4 (DPP4) inhibitors [40][41][42][43][44]. These agents in combination with basal insulin may represent an alternative in patients with COVID-19 and mild to moderate hyperglycemia [33].…”
Section: Insulin Therapymentioning
confidence: 99%